An Efficient Selective Oxidation of Alcohols with Zinc Zirconium Phosphate under Solvent‐free Conditions. Issue 7 (8th July 2015) - Karimi, Hirbod
Abstract Zinc zirconium phosphate (ZPZn) nanoparticles have been used as an efficient catalyst for the selective oxidation of a wide range of alcohols to their corresponding ketones or aldehydes using H2O2 as an oxidizing agent without any organic solvent, phase transfer catalyst, or additive. The steric factors associated with the substrates had a significant influence on the reaction conditions. The results showed that this method can be applied for chemoselective oxidation of benzyl alcohols in the presence of aliphatic alcohols. The catalyst used in the current study was characterized by ICP‐OES, XRD, N2 adsorption‐desorption, NH3‐TPD, Py‐FTIR, SEM, and TEM. These analyses revealed that the interlayer distance in the catalyst increased from 7.5 to 8.7 Å when Zn2+ was intercalated between the layers, whereas the crystallinity of the material was reduced. This nanocatalyst could also be recovered and reused at least seven times without any discernible decrease in its catalytic activity. This new method for the oxidation of alcohols has several key advantages, including mild and environmentally friendly reaction conditions, excellent yields and a facile work‐up.